Improving Students’ Vocabulary through Android-based English Textbook; An Experimental Study - Virgi Septiara Fajrin; Mubarok, Husni (LPPM Universitas Advent Indonesia, 2025)
This study was conducted to determine whether Android-based English textbooks (ABET) could enhance the vocabulary skills of tenth-grade students at MA Miftahul Ulum. This study employed a pre-experimental approach featuring a one-group design that includes pre-tests and post-tests. The population was 30 students, and the sample used saturation sampling. Data was gathered through a multiple-choice test consisting of 45 questions in total. Data was gathered using a pre-test, an ABET treatment session, and a post-test to measure students' vocabulary improvement. This study employed statistical data analysis methods, including descriptive statistics and paired samples t-test, utilizing SPSS software. The results showed that the effect of education on students' vocabulary was statistically significant; the students' mean score in the post-test (73.60) significantly exceeded the pre-test mean (48.26), and the t-test computation yielded a significance value of 0.000. The figure falls below the 0.05 threshold, indicating statistical significance. The results showed that students' attention and vocabulary increased significantly from the Android-based learning media ABET, so it can be an alternative choice to printed materials. This study suggests that the use of digital textbooks should be expanded to prove a more dynamic and accessible EFL educational environment.